The effects of Foreign Direct Investment (FDI) inflows to the host country's economic growth: an evidence of Malaysia / Norhafizawati Ab Wahab - Ab Wahab, Norhafizawati (Faculty of Business and Management, 2007)
This study is aim mainly to focus on the effects of foreign direct investment (FDI) inflows to the host country’s economic growth taking Malaysia as an evidence. The purpose of this study is to identify which macroeconomics variables between export, unemployment rate and gross domestic product (GDP) are most significantly affected by FDI inflows. In order to measure the effects of FDI inflows, this study took 37 numbers of observations in yearly basis data from 1970 until 2006. Pearson Correlation Coefficients and Simple Linear Regression model were used in order to analyze the relationship of FDI inflows with export, unemployment rate and GDP. Finally, the findings from this study show that all of the variables have relationship with FDI inflows. However, GDP has been proved to be the most significantly affected by FDI inflows.